Effect of K2O/Na2O on fusion behavior of coal ash with high silicon and aluminum level. (1st April 2020) - Li, Xiaoming; Zhi, Lifei; Shi, Wenju; Kong, Lingxue; Bai, Jin; Yu, Jianglong; Reinmöller, Markus; Guhl, Stefan; Meyer, Bernd; Li, Wen
Highlights: "Mixed-alkali effect" explains the influence of K2 O/Na2 O on ash fusibility well. SiO2 -KAlSiO4 -NaAlSiO4 phase diagram was constructed to reveal the competition effect between K2 O and Na2 O on AFTs. The fusion process can be divided into two stages based on variation rate of ash cone height. Abstract: Ash fusion temperatures (AFTs) are widely used for evaluation of fusibility of coal ash for combustion and gasification. K2 O and Na2 O is regarded as the effective component to enhance the ash fusibility for slag tapping. The combination of K2 O and Na2 O may enhance the flux efficiency. In this work, the effect of K2 O/Na2 O mass ratio on fusion behavior of coal ash with high silicon and alumina level was evaluated by the height variation of ash cone during heating. The results showed that AFTs and theoretical fusion range (Tliq -Tini ) decreased quickly and then increased slowly as the K2 O/Na2 O mass ratio in the coal ash was reduced. The sub-liquidus phase changed from mullite into feldspar, which was responsible for change of AFTs. Meanwhile, most of K element occurred in leucite (KAlSi2 O6 ) and the rest existed in nepheline (KAlSiO4 ), but Na almost existed in nepheline (NaAlSiO4 ). The competition effect between K2 O and Na2 O on AFTs was reflected by KAlSiO4 /NaAlSiO4 in nepheline, so the SiO2 -KAlSi2 O6 -NaAlSi2 O6 ternary phase diagram was constructed, which well explained the variation of AFTs caused by K2 O/Na2 O mass ratio. Meanwhile, the fusion process was divided into two stages based on variation rate of ash cone height. At first stage, the amount of liquidus phase is limited and the viscosity is high, so only a low shrinkage rate of ash cone exhibits. However, at the second stage, high shrinking rate is caused by not only the rapid increase of slag content but also the sharp decrease of viscosity besides, the addition of K2 O/Na2 O change ash fusion process from "melting-dissolving" into "softening-melting".